2021
DOI: 10.1007/s10956-021-09936-x
|View full text |Cite
|
Sign up to set email alerts
|

Professional Growth of Novice and Experienced STEM Teachers

Abstract: The first years of teaching are crucial for novice teachers’ integration into and retainment in the education system. The support they receive from experienced teachers impacts their professional development. Science, technology, engineering, and mathematics (STEM) teachers require specialized support from domain-specific mentors. In this study, we examined how a three-level mentoring support system contributes to STEM novice teachers’ professional growth (PG) and to their mentors. The support system levels ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…The findings of the study conformed to several studies that show that older teachers are more effective than younger ones [56] [34] [9] [2]. However, some studies revealed that age is not significantly related to the PCK of science teachers [54].…”
Section: Difference In the Extent Of Pck Practice Of Science Teachers...supporting
confidence: 87%
“…The findings of the study conformed to several studies that show that older teachers are more effective than younger ones [56] [34] [9] [2]. However, some studies revealed that age is not significantly related to the PCK of science teachers [54].…”
Section: Difference In the Extent Of Pck Practice Of Science Teachers...supporting
confidence: 87%
“…It seems obvious, therefore, that there should be induction programs aimed precisely at making this process more manageable. Several experiences from around the world have corroborated the usefulness of this type of practice (Akiri and Dori, 2022; Alexopoulos et al. , 2022; Kearney, 2021; Kyrou et al.…”
Section: Discussionmentioning
confidence: 86%
“…It seems obvious, therefore, that there should be induction programs aimed precisely at making this process more manageable. Several experiences from around the world have corroborated the usefulness of this type of practice (Akiri and Dori, 2022;Alexopoulos et al, 2022;Kearney, 2021;Kyrou et al, 2020). In particular, in Spain, after passing the competitive examination for entry to the teaching profession as a civil servant, there is a one-year traineeship as an introduction to teaching (Eurydice, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…This gives an opportunity to adjust assignments according to the group in question, as well as to be a teacher who understands early in the course the needs of the group. Beginning STEM teachers not infrequently need effective support during the instructional process 59 ; a test can help.…”
Section: Discussionmentioning
confidence: 99%